Reservoir Formation Damage Due to Water Injection Wells - Fallah, Hooman; Afkhami, Mohammad; Ahmadi, Ali; Jalali, Reza (IJRDO-Journal of Applied Science, 2016)
Water injection is an integral constituent of most field development scenarios, It has been considered forenhanced oil recovery (the heavy oil). This injection may take place for secondary recovery and pressuremaintenance such as sea water injection associated with most injection schemes is injectivity decline; wherethe rate of injection decreases over time at a given constant injection pressure gradient. The phenomenonof injectivity decline is comprised of multiple phenomena such as internal filtration, external filter cakebuild-up, fracture propagation, relative phase changes within the matrix rock and the associatedpermeability decline due to each of the described phenomena.In this thesis addresses some of the key phenomena associated with injectivity decline. Most of the transportmodels describing the transport and capture of contaminants in the injection fluid within the matrix porousmedium. The external filter cake build-up, an erosion model was derived based on the interaction of forcesacting on a retained particle on the surface of the external-filter cake for both rectilinear and radialgeometries. We postulate that during some initial period, an internal filter cake is formed. We refer to thetime at which no more particles invade the rock, i.e. the time at which the initial layer of external filter cakeis completely formed, as the transition time.The prediction of particle capturing and particle retention by mathematical model is an essential stageduring planning and design of above-mentioned industrial processes.